Progress Towards Parity: Female Representation in the American Society of Ophthalmic Plastic and Reconstructive Surgery. Issue 3 (14th July 2020) - Azad, Amee D.; Rosenblatt, Tatiana R.; Chandramohan, Arthika; Fountain, Tamara R.; Kossler, Andrea L.
Abstract : Purpose: To report female representation within the American Society of Ophthalmic Plastic and Reconstructive Surgery (ASOPRS) at all levels of career achievement over 50 years. Methods: Data were extrapolated from published ASOPRS directories and the 50th anniversary booklet. Fellowship, membership, leadership, and awards data were evaluated over 5 decades. Comparisons were made between the first and second 25 years, proportions of early and late career achievements, and time to career progression between males and females. Results: During the first decade, 5.6% of ASOPRS fellows were female (n = 2), which rose to 6.6% (n = 8), 17.6% (n = 32), 22.4% (n = 35), and 39.4% (n = 97) in the second, third, fourth, and fifth decades, respectively. These patterns were echoed in ASOPRS membership. When comparing the first half (1969–1994) to the second half (1995–2018), fellowship (10.5% vs. 30.0%, p < 0.001), membership (8.0% vs. 30.3%, p < 0.001), early career awards (5.6% vs. 28.9%, p = 0.047), program directorship (0.0% vs. 15.7%, p = 0.017), and executive committee female representation (4.5% vs. 16.8%, p < 0.001) increased significantly. However, females were proportionally underrepresented as program directors ( p = 0.003), late career award winners ( p = 0.001), executive committee members ( p < 0.001), and presidents ( p = 0.020). Among those reaching leadership positions, females took longer than males to become program directors by a median of 4 years ( p = 0.025). Conclusions: There has been a steady increase in female representation in ASOPRS fellowship training and membership. While significant progress has been made, growth in female leadership and award recognition is still needed. Abstract : Female representation in the American Society of Ophthalmic Plastic and Reconstructive Surgery has been steadily increasing over the last 50 years. This paper highlights the progress towards parity in fellowship and membership representation and identifies areas for growth in leadership and award recognition.